Peningkatan Kesadaran dan Deteksi Dini Kanker Leher Rahim dan Payudara pada Perempuan melalui IVA dan SADANIS di Puskesmas 1 Wedung, Demak - Cahyo Wulandari; Vina Annisa Putri; Siti Aisyah; Cinta Aulia Shafira Panggabean; M. Zahrandika Putra Raihan (Direktorat Pengabdian kepada Masyarakat, 2026)
In 2020, cancer was one of the six leading causes of death and ranked second as the leading cause of death globally. In Indonesia, breast cancer and cervical cancer are the most common types of cancer among women, with a mortality rate of 70% of all detected cases. The IVA (Visual Inspection with Acetic Acid) and SADANIS (Clinical Breast Examination) methods are effective initial steps for detecting signs and symptoms of cancer in women. This activity aims to increase knowledge and awareness among the public, particularly women, about the importance of early detection of cervical and breast cancer. Through this program, it is hoped that women will better understand the risks and be able to recognize early warning signs. The methods used include reproductive health counseling for women aged 30 to 50 years, followed by cervical and breast cancer screenings. Additionally, the program includes a family planning safari that offers free contraceptive services, such as implants and IUDs, as an additional preventive measure. This activity, held at Puskesmas 1 Wedung, was attended by 14 female participants. The screening results using the IVA and SADANIS methods showed that all participants were negative for cancer indications and had no lumps in their breasts. Based on these results, it can be concluded that routine early detection is crucial for maintaining health and preventing the progression of the disease. Through early detection, appropriate treatment steps can be taken as early as possible, thereby minimizing the risk of complications and death due to cancer. This activity did not include a quantitative evaluation such as pretest-posttest; therefore, changes in knowledge and behavior could not be measured objectively. The results presented are descriptive and reflect immediate program outcomes.